2018
DOI: 10.1002/apj.2267
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution of bubbles in agitated viscous Newtonian and non‐Newtonian solutions

Abstract: The effects of impeller type, Newtonian shear thinning liquid viscosities, and noncoalescing conditions on the impeller gas cavities, impeller power consumption, and Sauter mean bubble diameter (d 32 ) in a multiphase agitated vessel were systematically studied. An underwater recording technique was used to study gas cavities and bubble size in various operating and design conditions. The gas cavity images were used to relate d 32 to gas cavity structure. It was observed that d 32 values increase with an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…If non-Newtonian systems in stirred vessels are considered, available data is much more limited, and existing empirical correlations are derived from the-oretical considerations (Garcia-Ochoa and Gomez (2009)). As pointed out by Momiroski et al (2018), current techniques are not suitable to measure bubble size in highly viscous and opaque fluids in aerated stirred tanks. In their work, they measured the bubble size in the impeller discharge region in shear-thinning solutions; however, the maximum superficial gas velocity they investigated was relatively low, equaling 3 mm s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…If non-Newtonian systems in stirred vessels are considered, available data is much more limited, and existing empirical correlations are derived from the-oretical considerations (Garcia-Ochoa and Gomez (2009)). As pointed out by Momiroski et al (2018), current techniques are not suitable to measure bubble size in highly viscous and opaque fluids in aerated stirred tanks. In their work, they measured the bubble size in the impeller discharge region in shear-thinning solutions; however, the maximum superficial gas velocity they investigated was relatively low, equaling 3 mm s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Khalili et al [20] studied the agitation effect on the bubble diameter and observed that even though the impeller rotation affected the Sauter mean bubble diameter, it did not change the number of bubble classes in the mixing system. The bubble size distribution, in turn, depends on the cavity structure for a given impeller type, gas flow rate, and impeller speed, as presented by Momiroski et al [65]. Their results also indicated that hollow blade turbines (HBT) generated smaller mean bubble sizes compared to Rushton turbines (RT).…”
Section: Single Impellersmentioning
confidence: 80%
“…High mass transfer requires a large interfacial area that can be achieved by decreasing the bubble mean diameter. However, the determination of the bubble size distribution is complex, and it is even more challenging in the non-Newtonian media [65]. In this case, the shear rate variation throughout the mixing system promotes a non-uniform bubble size distribution in which lower bubble mean sizes are observed near the impeller region due to higher shear rate in this region [66].…”
Section: Bubble Mean Sizementioning
confidence: 99%
See 2 more Smart Citations